The impact of the insurance market on economic growth: evidence from Türkiye - KAYA, MUHAMMED VEYSEL; UMUT, MUHARREM; AKKURT, ENES (Ekonomia i Prawo. Economics and Law, 2025)
Motivation: The insufficient academic studies in the field of insurance in Türkiye and the lack of studies in the literature aimed at identifying the relationship between the financial market and the economic market have motivated this study. Aim: One of Türkiye’s emerging financial markets is the insurance market. This study aims to determine the direction of the relationship between the growth of Türkiye’s emerging insurance market and economic growth. Results: The analyses have revealed that there is either a unidirectional causal relationship between the variables used and economic growth or, in some cases, no causal relationship at all. Particularly, the results indicate a unidirectional causality and both short-term and long-term relationships between GDP and the variables of total premium production, claim payments, and market share. However, no causal relationship was found between the GDP variable and operating expenses, with only a long-term relationship with economic growth detected, and no short-term relationship identified. The research provides valuable insights for future research plans by revealing the interaction between the insurance sector in Türkiye and economic growth.